2003
DOI: 10.1055/s-2003-40206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Paramagnetic Carbo-and Heterocycles

Abstract: S y n t h e s i s o f P a r a m a g n e t i c C a r b o -a n d H e t e r o c y c l e s Abstract: Starting from paramagnetic b-bromo-a,b-unsaturated aldehyde 1, b-bromo-a,b-unsaturated nitrile 2 and diene 3 heterocycles 4-10 and carbocycles 12-14, 16, and 17 were synthesized with simple procedures in the presence of a nitroxide moiety. A complex-forming paramagnetic phenanthroline 19 is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…4 Conducting syntheses in the presence of the free radical can be surprisingly facile. Seminal work by Hideg and Kálai et al demonstrated the compatibility of the nitroxide moiety with an extensive variety of fundamental synthetic reactions, 5 including Diels–Alder, 6 7 Friedel–Crafts, 8 aldol condensation, 9 Claisen rearrangement, 10 and Michael-type additions. 11 Since then, this compatibility has been shown to also include Van Leusen, 12 Pd-catalysed cross-coupling, 13 14 15 16 click chemistry, 17 18 19 halogenation, 20 21 22 diazotation, 23 nitration, 24 25 and carbodiimide coupling.…”
mentioning
confidence: 99%
“…4 Conducting syntheses in the presence of the free radical can be surprisingly facile. Seminal work by Hideg and Kálai et al demonstrated the compatibility of the nitroxide moiety with an extensive variety of fundamental synthetic reactions, 5 including Diels–Alder, 6 7 Friedel–Crafts, 8 aldol condensation, 9 Claisen rearrangement, 10 and Michael-type additions. 11 Since then, this compatibility has been shown to also include Van Leusen, 12 Pd-catalysed cross-coupling, 13 14 15 16 click chemistry, 17 18 19 halogenation, 20 21 22 diazotation, 23 nitration, 24 25 and carbodiimide coupling.…”
mentioning
confidence: 99%